Transcriptomics analysis of Psidium cattleyanum Sabine (Myrtaceae) unveil potential genes involved in fruit pigmentation - Vetö, Nicole M. (2020)
Psidium cattleyanum Sabine is an Atlantic Forest native species that presents some populations with red fruits and others with yellow fruits. This variation in fruit pigmentation in this species is an intriguing character that could be related to species evolution but still needs to be further explored. Our goal was to provide genomic information for these morphotypes to understand the molecular mechanisms of differences in fruit colour in this species. In this study, we performed a comparative transcriptome analysis of red and yellow morphotypes of P. cattleyanum, considering two stages of fruit ripening. The transcriptomic analysis performed encompassing leaves, unripe and ripe fruits, in triplicate for each morphotype. The transcriptome consensus from each morphotype showed 301,058 and 298,310 contigs from plants with yellow and red fruits, respectively. The differential expression revealed important genes that were involved in anthocyanins biosynthesis, such as the anthocyanidin synthase (ANS) and UDP-glucose:flavonoid-o-glucosyltransferase (UFGT) that were differentially regulated during fruit ripening. This study reveals stimulating data for the understanding of the pathways and mechanisms involved in the maturation and colouring of P. cattleyanum fruits and suggests that the ANS and UFGT genes are key factors involved in the synthase and pigmentation accumulation in red fruits.